Adherence to dietary recommendations of Italian pregnant women and sociodemographic characteristics and lifestyles: results of a cross-sectional study - De Pasquale, Lisa; Garuti, Caterina; Palandri, Lucia; Lucaccioni, Laura; Trevisani, Viola; Casalucci, Marta Anna; Cattini, Umberto; Facchinetti, Fabio; Iughetti, Lorenzo; Filippini, Tommaso; La Marca, Antonio; Bargellini, Annalisa; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Unhealthy dietary habits during pregnancy can lead to immediate and future adverse health consequences for mother and child. Italian Society of Gynaecology and Obstetrics (SIGO) promulgated nutritional recommendations to promote correct food intake for future mothers. The study aimed to assess the adherence to dietary recommendations during the 3rd trimester of pregnancy and to evaluate the role of maternal characteristics and lifestyles. Methods: This cross-sectional study investigated dietary habits in a sample of women representative of physiologic pregnancies (n=572, mean age 33.4±5.2 y) living in Modena (Italy). Maternal diet (food consumption frequency), lifestyles and sociodemographic features were assessed by a questionnaire. Descriptive statistics and bivariate associations (Chi-square tests) were performed. Results: Adherence to SIGO recommendations varied among food categories. The highest compliance was observed for coffee/tea (93.5%), alcohol (76.6%) and white meat (63.6%). Adherence between 40-60% were observed for sweets (45.1%), bread/pasta/cereals (48.6%) and processed meat (56.8%), while adherence between 20-40% was highlighted for cheese (24.5%), potatoes (25.7%), eggs (25.9%), legumes (28.8%), fruit/vegetables (32.5%) and fish/seafood (38.8%). The lowest adherence was reported for milk/yogurt (15.4%) and red meat (17.3%). Smoking, younger age, lower educational level and unemployment appeared negatively influence adherence, including fruit/vegetables, fish, processed meat, alcohol, tea/coffee and soft drinks. Conclusions: Adherence to dietary recommendations among Italian pregnant women appeared low and influenced by several socio-demographic features and lifestyles. Targeted interventions and public health strategies to enhance maternal nutrition need to be implemented or reinforced to sustain women and children health, especially in most vulnerable groups.